Association of Markers of Proinflammatory Phenotype and Beige Adipogenesis with Metabolic Syndrome in Chinese Centrally Obese Adults. (18th February 2018) - Leung, Wilson K. C.; Yu, Angus P.; Lai, Christopher W. K.; Siu, Parco M.
Abstract : Background . Visceral adiposity is associated with higher productions of C-reactive protein (CRP) and interleukin-6 (IL-6). Inflammation of obese adipose tissues could contribute to systemic metabolic dysregulation, especially thermogenic activity of white adipose tissues, namely, beige adipogenesis, characterized by altered irisin expression. Thus, we investigated the roles of inflammation and adipocyte beiging in Chinese centrally obese (CO) adults with metabolic syndrome (MetS). Methods. This cross-sectional study was conducted on 54 CO and 58 non-CO subjects drawn from 1492 Chinese people with age and sex matched during November 2010 and August 2013. Twenty (37.0%) of the CO subjects fulfilled the IDF worldwide definition of MetS. Serum CRP, IL-6, and irisin levels were examined. Results . Higher CRP and IL-6, but lower irisin, levels were manifested in MetS versus non-MetS subjects with or without CO. Multiple linear regression identified high-density lipoprotein cholesterol level as the only independent risk factor for irisin level. Categorized by median of CRP and IL-6 levels, a lower irisin level was only observed in high CRP group. Conclusion . Under the condition of central obesity, chronic inflammation and impaired beige adipogenesis are associated with MetS in Chinese adults.